A Case Report on Combination Therapy Using a Composite Allograft Containing Mesenchymal Cells With an Amnion–Chorion Barrier to Treat a Mandibular Class III Furcation. Issue 2 (1st May 2013) - Rosen, Paul S.
Abstract : Introduction: Maintaining molars with Class III furcation invasion remains one of the greatest challenges in periodontics. Surgical treatment of these areas by any means has been disappointing. This case report describes a successful combined regenerative approach using a composite allograft with mesenchymal stem cells along with a barrier derived from human amnion–chorion to close a Class III furcation. Case Presentation: The patient was a 62‐year‐old white male referred for the treatment of his periodontal and dental implant needs. The mandibular left required functional crown lengthening for the two premolars along with management of the Class III furcation on the first molar. The unopposed second molar with both an advanced osseous lesion and 1+ degree mobility was to be extracted. Surgical exposure allowed the furcation to be thoroughly scaled and planed, treated with tetracycline for root modification, followed by intramarrow penetration and recombinant platelet‐derived growth factor applied to the roots. A composite allograft containing mesenchymal cells was used to fill the defect, and it was layered by a barrier derived from human amnion–chorion tissue. The flaps were coronally advanced and sutured with expanded polytetrafluoroethylene. Six months after the completion of surgery, the furcation was closed to a Nabers probe from both the buccal and lingual aspects and radiographically, the area was radiopaque suggestive of bone fill/containment. Conclusion: This case report demonstrates the closure of a Class III furcation based on horizontal probing and radiographic bone fill, giving hope that this combined approach for regeneration may hold promise for treating this most challenging of clinical dilemmas.